Phase behaviour of the restricted primitive model - Patsahan, O.V. (Condensed Matter Physics, 2004)
The phase behaviour of the restricted primitive model (RPM) is studied using a microscopic approach recently developed for the description of phase transitions in binary fluid mixtures. For the model we obtain the explicit expression for the functional of the grand partition function. Based on the functional we calculate the phase diagram of the RPM in the high temperature approximation (HTA) and then we do this calculation taking into account the terms of the higher orders in the effective Hamiltonian. In both cases the phase diagrams demonstrate the gas-liquid (GL) and charge ordering phase instabilities. In the latter case, the obtained value for the GL critical temperature is in good agreement with the MC simulation data whereas the critical density is underestimated.